Influência da adição de macrofibras nas propriedades mecânicas e de desempenho de brita graduada tratada com cimento - Feldens, Nathani Eduarda de Andrades (2022)
The road mode is the largest among Brazilian modes of transportation, with a density of 0.2 km/km² of the country's territory. However, new investments in transportation infrastructure are needed to boost Brazil's economic development. The current scenario, however, is one of stagnation in the road sector, due to a shortage of resources. In this unfavorable context, new sidewalks must be designed with alternative materials capable of providing an adequate level of serviceability and economy, by reducing maintenance. The present study, therefore, is focused on the development of new materials for paving and, specifically, on the evaluation of reinforcement with polypropylene macrofibers, usually used in concrete, applied to a matrix of cement treated graded gravel (CTCS). The main objective is, from the definition of an optimum dosage, to verify the mechanical behavior of the reinforced material against the degradation caused by the fatigue phenomenon. Physical characterization tests of the materials, mechanical characterization and four point fatigue tests were performed for combinations between three cement percentages (3.4 and 5%) and three fiber percentages (0.1, 0.3 and 0.5%). The results state that the reference mixtures have the characteristics required to stabilize the graded gravel with the dosage used. The cement content has a direct influence on the results found, in relation to simple compression. The macrofiber, in turn, has a negative effect, causing a decrease in the result due to its characteristics of agglutination, however, produced a positive response when applied to the CTCS in order to reduce degradation caused by the fatigue phenomenon, providing a lengthening of the curves and delaying the rupture of the specimens.